Extended Theory of Planned Behaviour: Pengaruh Norma Subjektif, Media Sosial, dan Customer Experience Terhadap Niat Berkunjung Ulang - Herdhi Bayu Prasetyo; Yunita Anggarini; Diesyana Ajeng Pramesti (Jurnal Perilaku dan Strategi Bisnis, 2025)
Revisit intention is a crucial indicator of the success of a tourist destination, as it reflects both visitor satisfaction and positive impressions of their travel experiences. The primary factors influencing tourists’ revisit intention include customer experience and subjective norms, defined as individuals’ perceptions of social support. In addition, social media contributes to shaping subjective norms by facilitating the exchange of experiences and serving as an effective promotional tool, particularly among younger generations. This study aims to analyze the factors influencing tourists’ revisit intention to Mount Tidar in Magelang. A quantitative research design was employed using multiple linear regression analysis. Primary data were collected through a survey method, with respondents consisting of visitors aged over 17 years who had visited Mount Tidar more than once. The findings indicate that revisit intention is significantly influenced by social media and customer experience, whereas subjective norms have no significant effect. Nevertheless, when considered simultaneously, the three variables—subjective norms, social media, and customer experience—demonstrate a positive influence on revisit intention. The weak effect of subjective norms suggests that tourists’ decisions to revisit are less shaped by external influences, such as peers, groups, or family, and are instead more strongly determined by internal factors, particularly customer experience with the destination.